FILSAFAT JAWA DALAM SERAT WEDHATAMA - Sutrisna Wibawa (JURNAL IKADBUDI, 2013)
This study aims to explore and formulate a philosophical concepts of Javanese Philosophy in Serat Wedhatama. The data sources were Serat Wedhatama. The data were analyzed using a hermeneutics method. The  findings as follows Serat Wedhatama contains noble teachings to develop the spiritual aspect which became oneof the Javanese’s basic spiritual activityappreciations. The final of spiritual activity which taughtby Serat Wedhatama is to find the true life, better self-understanding, manunggaling kawula-Gusti, and to receive the grace of God by seeing the secrets of supernatural things. This is in accordance with the Javanese’s philosophy, which emphasizes the importance of the perfection of life (Ngudi kasampurnan), that humanis alwaysconnected to the environment, namely God and the universe, and believes the unity of Him (manunggaling kawula Gusti). Key words: Javanese Philosophy, Serat Wedhatama